Simulation and optimization of gasoline autothermal reformer for fuel cell applications - Aziz, Farhana (2006)
Fuel cell systems are being developed for powering clean, efficient automobiles of the future. The proton exchange membrane fuel cell (PEMFC) systems being developed for such use require a fuel gas that is either pure hydrogen, or a gas mixture that contains significant concentration of hydrogen. Thus, the vehicles with gasoline as the on-board fuel use a fuel processor, also referred to as an autothermal reformer, to convert gasoline to a fuel gas and reformate, that contains hydrogen, carbon dioxide, water vapor, and nitrogen, with trace levels of other species, such as carbon monoxide and unconverted gasoline. With the help of Aspen HYSYS 2004.1 the steady state model has been develop to analyze the fuel processor and total system performance. In this case study, the PEM fuel cell system consists of the fuel processing and clean-up section, PEM fuel cell section and auxiliary units. While the fuel processing and clean-up section consists of Autothermal Reformer, High-temperature Shift, Medium-temperature Shift, Low-temperature Shift, and Preferential Oxidation. The purpose of this study is to identify the influence of various operating parameters such as A/F and S/F ratio on the system performance that is also related to its dynamic behaviours. From the steady state model optimization using Aspen HYSYS 2004.1, an optimised reaction composition, in terms of hydrogen production and carbon monoxide concentration, corresponds to A/F ratio of 18.5 and S/F ratio of 9.0. Under this condition, n-octane conversion of 100%, H2 yield of 42% on wet basis and carbon monoxide concentration of 7.56ppm can be achieved. The fuel processor efficiency is about 80.41% under these optimised conditions.